Answer:
(7w - k)(4x + y)
Step-by-step explanation:
Factor by grouping is best for this expression. To factor by grouping, group pairs of terms with parenthesis. Then find the GCF in each pair. If the parenthesis match after, the factoring is complete.
28xw + 7wy - 4kx - ky
(28xw + 7wy) + (- 4kx - ky)
7w(4x + y) - k (4x + y)
The factors are (7w - k)(4x + y).
Answer:
52-13 = 39
Step-by-step explanation:
This is simple, next time use a calculator and calculate yourself
Answer:
true, false, and false
Step-by-step explanation:
Answer:
The answer to your question is: (x + 2)(3x - 1) = 0
x1 = -2
x2 = 1/3
Step-by-step explanation:
3x² + 5x − 2 = 0
Multiply 3 x -2 = -6
Find two numbers that added = +5 and multiply -6
These numbers are +6 and -1
Then:
3x² + 6x -1x − 2 = 0
Factorize 3x (x + 2) - 1(x + 2) = 0
Factorize again (x + 2)(3x - 1) = 0
Finally
x + 2 = 0 3x - 1 = 0
x = -2 x = 1/3